The Reality of The Father’s Archetype in Modern Indonesian Literature: Carl Jung’s Analytic Psychological Study - Isnaini Yulianita Hafi; Syukrina Rahmawati (HUMANIKA, 2022)
The purpose of this study is to describe the correlation between the results of literary research about the archetype symbol of the father complex with Jung's analytic psychological theory. Known literary works are concrete evidence of the existence of someone who tries to show his presence in the midst of social life which is full of symbols and myths. Based on the concept of the father complex that appears because of the archetypal characters, it has been clearly seen from the ancestors' time that an unconscious activity forms an adaptive psyche working system before the birth of consciousness and hereditary. This study uses a Literary Psychology approach. The research method used is descriptive qualitative with Jung's analytical psychology theory in studying the novels Koplak by Oka Rusmini and Ayah by Andrea Hirata. The research results can be seen through the four aspects of archetypes according to Jung: a father and a leader who is full of responsibility, a father and a wise man, a romantic and assertive father, and a brave father who is willing to sacrifice for his children. The concept of the father complex in the character of the father in the novel Koplak and Ayah has a difference in psychological conditions and social realities that are raised through stories. The implications of this research can be realized by realizing the concept of the father archetype which shows the existence of a basic personality in society in general.